Kochland : the secret history of Koch Industries and corporate power in America - Leonard, Christopher, 1975- (Simon & Schuster, 2019)
Uses the extraordinary account of how the biggest private company in the world grew to be that big to tell the story of modern corporate America. The annual revenue of Koch Industries is bigger than that of Goldman Sachs, Facebook, and U.S. Steel combined. Koch is everywhere: from the fertilizers that make our food to the chemicals that make our pipes to the synthetics that make our carpets and diapers to the Wall Street trading in all these commodities. But few people know much about Koch Industries and that's because the billionaire Koch brothers want it that way. For five decades, CEO Charles Koch has kept Koch Industries quietly operating in deepest secrecy, with a view toward very, very long-term profits. He's a genius businessman: patient with earnings, able to learn from his mistakes, determined that his employees develop a reverence for free-market ruthlessness, and a master disrupter. These strategies have made him and his brother David together richer than Bill Gates. But there's another side to this story. If you want to understand how we killed the unions in this country, how we widened the income divide, stalled progress on climate change, and how our corporations bought the influence industry, all you have to do is read this book. Seven years in the making, Kochland reads like a true-life thriller, with larger-than-life characters driving the battles on every page. The book tells the ambitious tale of how one private company consolidated power over half a century--and how in doing so, it helped transform capitalism into something that feels deeply alienating to many Americans today.